Motivasi Akademik pada Siswa SMA di Kalimantan Barat - Purba, Novia Sri Parindu; Gunawan, William (Noetic Psychology, 2014)
AbstrakAcademic motivation showed inner drive within every students to achieve highest achievement. They were internal and external factor that influence ones academic motiation.ÃÂ This research aime to explore and describe academic motivation in high school student in West Borneo.ÃÂ ÃÂ Using cluster disproportionate stratified random sampling, 184 highschool student from three different area in West Borneo selected as the sample. Academic motivation measured using the LOMOT (Low Motovation) dimension of SMALSI (Student Motivation and Learning Style Inventory (SMALSI). Result found that student academic achievement in West Borneo is in medium level. Result alsho showedÃÂ there was a significant different in academic motivation between student in the Pontianak city,Singkawang region and Kembayan districk.ÃÂ ÃÂ Kata kunci : academic motivation, highschool student, West Borneo